Morphology of left ventricular outflow tract structures in patients with subaortic stenosis and a ventricular septal defect. Issue 3 (September 1994) - Kitchiner, D; Jackson, M; Malaiya, N; Walsh, K; Peart, I; Arnold, R; Smith, A
Abstract : OBJECTIVE--To compare the incidence and prognosis of subaortic stenosis associated with a ventricular septal defect and to define the morphological basis of subaortic stenosis. DESIGN--Presentation and follow up data on 202 patients with subaortic stenosis seen at the Royal Liverpool Children's Hospital between 1 January 1960 and 31 December 1991 were reviewed. Survivors were traced to assess their current clinical state. Necropsy specimens of 291 patients with lesions associated with subaortic stenosis were also examined. RESULTS--In the clinical study; 65 (32.1%) of the 202 patients with subaortic stenosis had a ventricular septal defect (excluding an atrioventricular septal defect). 32 of these patients had a short segment (fibromuscular) subaortic stenosis. 33 had subaortic stenosis produced by deviation of muscular components of the outflow tracts. In 17 patients (51.5%) this was caused by posterior deviation or extension of structures into the left ventricular outflow tract, resulting in obstruction above the ventricular septal defect. In the other 16 patients (48.5%) there was over-riding of the aorta with concordant ventriculoarterial connections, (without compromise to right ventricular outflow) producing subaortic stenosis below the ventricular septal defect. Additional fibrous obstruction occurred in 39% of the patients with deviated structures. The age at presentation was lower (P < 0.01) in patients with deviated structures (median (range) 0.4 (0 to 9.2) months) than in those with short segment obstruction (median (range) 4.2 (0 to 84.9) months). The incidence of aortic arch obstruction was higher (P < 0.002) in patients with deviated structures than in those with short segment obstruction (38%). In the morphological study 35 pathological specimens showed obstructive muscular structures in the left ventricular outflow tract either above or below the ventricular septal defect. 16 had either posterior deviation of the outlet septum or extension of the right ventriculoinfundibular fold, or both of these together into the left ventricle. 19 had anterior deviation of the outlet septum into the right ventricle with overriding of the aorta (without compromise to right ventricular outflow). The earliest age at which additional fibrous obstruction was seen was 9 months. The aortic valve circumference was small in 18% of specimens. FOLLOW UP--The median (range) duration of follow up in survivors from the clinical study was 6.6 (1 to 25.7) years. 16 patients with deviated musculature (49%) and 16 with short segment fibromuscular stenosis (50%) underwent operation for subaortic stenosis. Patients with deviated structures were younger at operation than those with short segment stenosis (P < 0.005). Patients with posterior deviation or extension of structures into the left ventricular outflow tract underwent operation for subaortic stenosis more frequently (P < 0.05) than those with anterior deviation of the outlet septum and aortic override. The ventricular septal defect required surgical closure more frequently (P < 0.005) in patients with deviation (93.9%) than in those with short segment obstruction (21.9%). There was no significant difference in the mortality between patients with deviation (27%) and those with short segment obstruction (12%). CONCLUSIONS--32% of patients in the clinical study with subaortic stenosis had a ventricular septal defect. Only 51% of these had obstructive and deviated muscular structures in the left ventricular outflow tract. These patients had a significantly higher incidence of aortic arch obstruction and required surgery for subaortic stenosis at a younger age than those with short segment obstruction. The ventricular septal defect also required surgical closure more frequently in those patients with deviation. The morphological study defined the two sites of obstruction. The presence or absence and type of deviation should be clearly defined in all patients with a ventricular septal defect,